Knee joint flexion moment during the pushing phase reduces the negative effective force in bicycle pedalling. - Yamaguchi, Y.; Watanabe, K.; Ohishi, K.; Fukuda, W.; Nishiyama, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
Pedalling skills are evaluated using the total negative effective force (TNEF) that occurs in the pulling phase (180-360° of crank rotation when 0° is top dead center). The aim of this study was to obtain data that might help cyclists to reduce TNEF and thus improve pedalling skills. We examined the relationship between TNEF and lower joint moments or pedal force data through full crank rotation. Fifteen male cyclists performed constant pedalling at 80%Vo2peak and 90 rpm. Pedal force and kinematic pedalling data were measured by a pedal-shaped force platform (1000 Hz) and by a 3D motion capture system (200 Hz). The average value of TNEF was -553.0 ± 277.1 N and the phase that was 180.6 ± 8.1?307.7 ± 86.3° of crank rotation was marked. At 60-310° of crank rotation, there was a correlation between knee joint moment and TNEF (p<0.05). Furthermore, at 40-100° of crank rotation there were positive correlations between the increase of hip joint extension moment and the decrease of knee joint extension moment or the increase of knee joint flexion moment (p<0.05). These results suggest that generation of hip extension moment in the pushing phase contributes to an increase of knee flexion moment, consequently reducing TNEF in the pulling phase.